Rydberg atoms and electron transfer to the continuum spectra. - Nemirovsky, J. B. E.; Meckbach, W.; Focke, P. (American Chemical Society, 1983)
Fil: Nemirovsky, J. B. E. Comisión Nacional de Energía Atómica; Argentina